(untitled) (Modern education and development, 2025)
Software requirements serve as the foundation for successful software development, ensuring alignment between stakeholders’ needs and system functionality. This paper explores the different levels of software requirements, including business, user, and system requirements, as well as their hierarchical structure. It also discusses best practices for requirement elicitation, specification, and validation to enhance software quality and project success.